Perlecan and the Blood-Brain Barrier: Beneficial Proteolysis? - Roberts, Jill; Kahle, Michael P.; Bix, Gregory J. (Frontiers in Pharmacology, 2012)
The cerebral microvasculature is important for maintaining brain homeostasis. This is achieved via the blood-brain barrier (BBB), composed of endothelial cells with specialized tight junctions, astrocytes and a basement membrane. Prominent components of the basement membrane extracellular matrix (ECM) include fibronectin, laminin, collagen IV and perlecan, all of which regulate cellular processes via signal transduction through various cell membrane bound ECM receptors. Expression and proteolysis of these ECM components can be rapidly altered during pathological states of the central nervous system. In particular, proteolysis of perlecan, a heparan sulfate proteoglycan, occurs within hours following ischemia induced by experimental stroke. Proteolysis of ECM components following stroke results in the degradation of the basement membrane and further disruption of the BBB. While it is clear that such proteolysis has negative consequences for the BBB, we propose that it also may lead to generation of ECM protein fragments, including the C-terminal domain V (DV) of perlecan, that potentially have a positive influence on other aspects of CNS health. Indeed, perlecan DV has been shown to be persistently generated after stroke and beneficial as a neuroprotective molecule and promoter of post-stroke brain repair. This mini-review will discuss beneficial roles of perlecan protein fragment generation within the brain during stroke.